Analyzing Students’ Perceptions of English Language Learning Through Online Learning Implementation - Asnawi Muslem; Ika Apriani Fata; Lathifah M.Nur (Jurnal Pendidikan Indonesia, 2022)
E-Learning also known as online learning became fully established during previous school year. This study aims to analyses students' perceptions of the usefulness of the E Belajar platform as a medium in the English online classroom, as well as the presences of English teachers. The method use is qualitative, consisting of a questionnaire and an interview. In a questionnaire, 56 students from one schools were asked to rate 20 statements on a five-point Likert scale. This school was chosen through purposive sampling because it used the E-belajar platform designed by ministry of education. In interview, there are five respondents through purposive sampling method to explore in depth usefulness of E-belajar and teachers presences. For the analysis, questionnaire data were analyzed using SPSS IBM Version 22, while the interview data were analyzed using thematic analysis. The result show that students preferred offline classes because the explanation of the learning materials was more obvious. In a face-to-face class, students can ask the teacher direct questions; they can maintain the offline class; they can gain more lessons in an offline class; they can understand more easily; they can enjoy themselves; the time in an offline class is more efficient; the explanation is clearer, and they can interact with the teacher. In summary, they acknowledged that E Belajar was beneficial in learning English and that teachers should consider using the digital platform during English online classes; however, teachers must guide and teach students accordingly.